The Role of Mitochondria in Vascular Calcification - Wang, Pengbo (J Transl Int Med, 2020)
Vascular calcification (VC) was defined as the ectopic deposition of calcium–phosphorus complexes on the blood vessel walls. It was a process involving multiple factors and mechanisms, covering the phenotype transition of vascular smooth muscle cells (VSMCs) and release of microvesicles. It was a common end-stage alteration of chronic diseases such as cardiovascular disease and chronic kidney disease. Increasing evidence indicates that mitochondria were involved in the development of VC. Mitochondria provided energy to cells, maintained the stability of cell functions, and participated in a variety of biological behavior. Oxidative stress, autophagy, apoptosis, and mitochondrial DNA (mtDNA) damage could affect the development of VSMCs calcification by alteration of mitochondrial function. This article reviewed the mechanism of calcification and the role of mitochondria in VC, aiming to raise a novel insight into drug development and clinical treatment.